2017
DOI: 10.4103/apc.apc_151_16
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous origin of right coronary artery causing myocardial ischemia in a young patient

Abstract: Anomalous right coronary artery from left coronary sinus can have dynamic narrowing and kinking causing symptoms of myocardial ischemia and sudden cardiac death. Surgical repair of the anomaly is required in the symptomatic patient because of risk of ischemia or ventricular arrhythmia. Asymptomatic incidentally diagnosed low-risk patients can be closely followed up with exercise restriction as per present guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…AORL is a rare congenital anomaly that can lead to myocardial ischemia and arrhythmia, increasing the risk of sudden cardiac death (41). Risk stratification and management can reduce the risk of ischemia in patients with AORL (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AORL is a rare congenital anomaly that can lead to myocardial ischemia and arrhythmia, increasing the risk of sudden cardiac death (41). Risk stratification and management can reduce the risk of ischemia in patients with AORL (41).…”
Section: Discussionmentioning
confidence: 99%
“…AORL is a rare congenital anomaly that can lead to myocardial ischemia and arrhythmia, increasing the risk of sudden cardiac death (41). Risk stratification and management can reduce the risk of ischemia in patients with AORL (41). The risk of sudden death depends on several anatomical features: an intramural course, a slit-like orifice, and an acute take-off angle (8,42).…”
Section: Discussionmentioning
confidence: 99%
“…Описаны различные типы хирургических методов восстановления кровотока обедненного русла коронарной артерии, которые включают в себя шунтирование, а также прямую реимплантацию ПКА в правый коронарный синус. Исследования показывают, что методы являются безопасными и демонстрируют хорошие среднеи долгосрочные результаты в отношении продолжительности и качества жизни пациентов [7,8].…”
Section: Discussionunclassified
“…Anomalous artery should be surgically repaired in the symptomatic patients because of risk of ischemia or ventricular arrhythmia and a close follow up is required in asymptomatic patients with exercise restriction as per present guideline. [44] Targeted patients for treatment are those whose anomalous artery is dominant, whose anomalous artery is having proximal intramural course and those who become symptomatic before 35 years of age. [41] Cheatham JP, et al reported origin of RCA from descending thoracic aorta and found atypical and elastotic changes and wall thickening in this RCA.…”
Section: Discussionmentioning
confidence: 99%